Analysis of factors driving foreign direct investment in the liquefied natural gas sector: case study Nigeria - Ogunsanwo, Babafemi (Cranfield University, 2024)
The empirical data revealed facts about factors driving foreign direct investment in the Nigerian LNG sector. This research uses the primary data gathered to contribute uniquely to empirical findings and knowledge. Some factors are deemed adequate when attracting foreign direct investment. The sufficient factors identified are political stability having a considerable impact on investor decisions, and long-term investment commitments in the LNG sector. The second significant factor identified is government efficiency, and the last factor is corruption with different components classified into two broad categories: attractors and deterrents. In this context, sufficiency is defined as the condition where FDI is likely to occur when a sufficient amount of the three factors listed are in place. Previous research has failed to understand and explain all three factors adequately. This is a new insight and contribution to knowledge. This study explains how factors driving foreign direct investment in Nigeria's liquefied natural gas sector have an impact. The research utilises the successful Bonny NLNG projects as an example to investigate the reasons behind the failure of the Olokola and Brass LNG projects, which were unable to reach a final investment decision. Distinct empirical analysis and research design show key factors driving foreign direct investment in the Nigerian LNG sector. Foreign direct investment is a type of cross-border investment that occurs when an investor from one country develops a long-term stake in and a considerable degree of control over an enterprise located in another country. Additionally, in green-field investment, foreign direct investment is in the form of a parent company establishing a subsidiary in another country and commencing operations from the ground up. The goal of foreign direct investment is the priority of gaining benefits from the investment, maximising return on investment, and seeking to control assets. It offers capital funding in exchange for an equity stake. LNG projects are capital- intensive, it requires sizable up-front financing. LNG project financing can be difficult due to their long-term nature, high costs, and associated risks. Securing funds from foreign lenders, equity investors, and project sponsors can be herculean, only the major exploration and production companies can achieve it. Thus, the research will focus on factors driving FDI in the LNG sector. Key stakeholders, policymakers, and investors will be interviewed. This thesis compiles feedback from stakeholders to identify the key factors driving foreign direct investment in Nigerian liquefied natural gas. The study presents evidence on the factors driving the inflow of foreign direct investment into the Nigerian LNG sector to policymakers, lawmakers, government executives, investors, community leaders, and financial institutions to test the effectiveness and efficiency of the research. The research design incorporates a mixed-method approach. Data collected through a questionnaire-based survey, semi-structured interviews, and focus group discussions, provide solid insight into the factors driving foreign direct investment in the Nigerian LNG sector. The questionnaire-based survey was used to gather data from 118 respondents. Data was gathered from 12 top gas stakeholders through semi-structured interviews, and an additional 4 executive participants participated in the focus group discussion. The study employs purposive sampling to identify the participants and interviewees. The fundamental value of the research comes from the real-world data it collects and the conclusions by looking at factors driving FDI in the LNG sector. Stakeholder theories were chosen as the theoretical framework for the research, emphasising the study's focus and applying the researcher's terminology to address the research questions. The literature review guided this decision. Nigeria's abundance of natural resources, particularly its substantial natural gas reserves, attracts foreign investors. The Nigerian gas sector presents opportunities for economic development, energy diversification, and environmental sustainability in the future. Nigeria has about nine hundred times more gas assets than the country's oil deposits, and its reputation as an oil producer overshadowed the gas sector's potential, even though the country's gas reserves are greater than oil. Gas asset is a necessary factor, but it is not sufficient enough to attract foreign direct investment.
Huo, Da - Associate Supervisor
Keywords: Assets; Economic; FDI; Gas Reserves; GDP; Legal Framework; Legislation; LNG; Macroeconomic; Political Stability; Regulations. Social Stability